Diagnostic Accuracy of Computed Tomography Scan in Detection of Upper Gastrointestinal Tract Injuries Following Caustic Ingestion - Bahrami-Motlagh, Hooman; Hadizadeh-Neisanghalb, Mohammad; Peyvandi, Hassan (Archives of Academic Emergency Medicine, 2017)
Introduction: Endoscopy is an invasive procedure and finding noninvasive alternative tools in detection of probable upper gastrointestinal (GI) tract injuries following caustic ingestion is an area of interest. The present study aimed to evaluate the screening performance characteristics of thoraco-abdominal computed tomography (CT) scan in this regard. Methods: This prospective cross sectional study was conducted on patients presenting to emergency department following acute caustic ingestion. The findings of CT scan and endoscopy regarding the presence of upper GI tract damage were compared and screening performance characteristics of CT scan were calculated using MedCalc software. Results: 34 patients with the mean age of 35.38±13.72 years were studied (58.8% male). The agreement rate between CT scan and endoscopy regarding the grade of esophageal and gastric injuries was moderate (K= 0.38; p = 0.001) and fair (K= 0.17; p = 0.038), respectively. The sensitivity and specificity of CT scan in detection of esophageal damage were 96.29) 79.11- 99.80) and 57.14 (20.23 - 88.19), respectively. These measures were 89.65 (71.50 - 97.28) and 40.00 (7.25 - 82.95), respectively for gastric damage. The area under the ROC curve of CT scan in detection of esophageal and gastric damages was 0.76 (95% CI: 0.52 – 1.00) and 0.64 (95% CI: 0.35 – 0.94), respectively. Conclusion: Based on the findings of the present study, CT scan could be considered as a sensitive tool in ruling out upper gastrointestinal mucosal injuries following acute caustic ingestions. However, the correlation between endoscopy and CT scan findings regarding the grading of injury is not high enough to eliminate the need for endoscopy.